The problem of creating and developing an integrated approach to standardization process of automated testing of turboexpanders - V. M. Mamedov; I. A. Arkharov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of the study is to discuss the issue of creating and developing an integrated methodological approach to testing and standardizing the process of testing turboexpanders based on automation equipment, taking into account the existing and potential demand for domestic turbine units by 2035 under the conditions of sanction pressure.Method. Identification of the problem and formation of an approach to its solution based on the existing domestic experience in testing turboexpanders, taking into account the introduction of automation tools and analysis of potential consumers of properly marked and structured data on the characteristics of the machine. Development and implementation of automatic regulation and control systems for low-temperature machines.Result. In accordance with the general classification of product testing, 9 types of research have been identified that are of scientific and practical interest in the experimental determination of the most relevant parameters of turboexpanders: isentropic efficiency, stability of the rotor and impellers, strength of impellers, vibration and noise characteristics.Conclusion. Based on the list of tests and the main characteristics of the machines, the place of application of experimental data was determined and requirements for means of conducting automated tests were formed in order to optimize cryogenic systems as a whole.